Cation-dependent Behavior of Aluminium under Pulsed Electrolysis - Marina Kubanova; Tatyana Yureva; Elena Yatsenko; Yash Vijay Kataria; Alexandra Kuriganova; Mikhail Lipkin; Nina Smirnova (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
For decades, chloride ions Cl⁻have been considered a key factor in the electrochemical behavior of aluminum in chloride electrolytes, including depassivation, pitting corrosion, and anodic dissolution. However, the influence of electrolyte cations has been considered secondary or ignored in most classical studies. In this study, we investigated the influence of electrolyte cations (MgCl2, CaCl2, SrCl2, BaCl2) on the electrochemical behavior of aluminum under the influence of an alternating symmetrical pulsed current with a density of 1 A.cm-2. The study found that in the presence of Ba2+ and Sr2+, aluminum is oxidized to form dispersed two-phase products AlOOH and Al(OH)3, with an average particle size of 1.9 and 2.2 nm for the AlOOH phase and 20.4 and 13.9 nm for the Al(OH)3 phase. In Mg2+ and Ca2+ chlorides, passivating films of Mg(OH)2 or Ca(OH)2 are formed, as well as layered double hydroxides – Mg6Al2(OH)16Cl2∙4H2O (Mg-Al LDH) or Ca2Al(OH)6Cl∙2H2O (Ca-Al LDH), respectively, which inhibit aluminum corrosion under pulse electrolysis conditions, even in the presence of activating Cl- ions. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).